A systems toxicology approach for comparative assessment: Biological impact of an aerosol from a candidate modified-risk tobacco product and cigarette smoke on human organotypic bronchial epithelial cultures. (March 2017) - Iskandar, Anita R.; Mathis, Carole; Schlage, Walter K.; Frentzel, Stefan; Leroy, Patrice; Xiang, Yang; Sewer, Alain; Majeed, Shoaib; Ortega-Torres, Laura; Johne, Stephanie; Guedj, Emmanuel; Trivedi, Keyur; et al.
Abstract: This study reports a comparative assessment of the biological impact of a heated tobacco aerosol from the tobacco heating system (THS) 2.2 and smoke from a combustible 3R4F cigarette. Human organotypic bronchial epithelial cultures were exposed to an aerosol from THS2.2 (a candidate modified-risk tobacco product) or 3R4F smoke at similar nicotine concentrations. A systems toxicology approach was applied to enable a comprehensive exposure impact assessment. Culture histology, cytotoxicity, secreted pro-inflammatory mediators, ciliary beating, and genome-wide mRNA/miRNA profiles were assessed at various time points post-exposure. Series of experimental repetitions were conducted to increase the robustness of the assessment. At similar nicotine concentrations, THS2.2 aerosol elicited lower cytotoxicity compared with 3R4F smoke. No morphological change was observed following exposure to THS2.2 aerosol, even at nicotine concentration three times that of 3R4F smoke. Lower levels of secreted mediators and fewer miRNA alterations were observed following exposure to THS2.2 aerosol than following 3R4F smoke. Based on the computational analysis of the gene expression changes, 3R4F (0.13 mg nicotine/L) elicited the highest biological impact (100%) in the context of Cell Fate, Cell Proliferation, Cell Stress, and Inflammatory Network Models at 4 h post-exposure. Whereas, the corresponding impact of THS2.2 (0.14 mg nicotine/L) was 7.6%. Highlights: A systems toxicology approach was applied to comprehensively assess the biological impact of a heated tobacco aerosol and cigarette smoke Series of experimental repetitions were conducted to increase robustness of the assessment Heated tobacco aerosol elicited less biological impact than cigarette smoke at similar nicotine concentration(s)